Cost analysis of different antibiotic brands available in indian market with reference to National List of Essential Medicines - Dinesh Kumar Meena; Mathaiyan Jayanthi (Wolters Kluwer Medknow Publications, 2021)
Background: About 60%-90% of healthcare spending in India is on medicine which is mainly out of pocket. Almost all the drugs including antibiotics are available as brands with variable cost. Indian government formulated National List of Essential Medicines (NLEM) to ensure availability of affordable medicines to the population. Prescribing drugs from NLEM and considering the cost of drug, especially antibiotics in practice, can reduce cost of treatment and patient's out-of-pocket expenditure. Objective: The objective of the study is to analyze cost variation of different antibiotic brands available in Indian market with reference to NLEM. Materials and Methods: List of antibiotics listed in the NLEM 2015, India, was prepared. Percentage cost variation and cost ratio of different brands of these antibiotics were calculated and compared. Results: We found 17 antibiotics listed in NLEM 2015. The number of brands varied from 2 to 102. We found wide cost variations among different brands of same antibiotics. Minimum cost variation was 7.34% (for ciprofloxacin 200 mg/100 ml vial) while maximum 1049.82% (for azithromycin 500 mg tablet). Conclusion: There is wide cost variation in different brands of same antibiotics listed in the NLEM. Prescribers should prescribe cheaper brands of antibiotics to ensure that patients complete the course of treatment and thus reduce development of resistance to antibiotics.